2019
DOI: 10.33552/ann.2019.05.000609
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Knowledge among Kuwait University Students: a Descriptive Study

Abstract: BackgroundDementia is a disease of cognitive decline that interferes with the person's daily functions and behavior. However, it is not a normal part of aging. Dementia is one of the World health organization's (WHO) public priorities as approximately 50 million people worldwide are currently living with dementia. According to WHO's results, dementia is the seventh highest cause of death [1]. Worldwide, every three seconds, there is a new case of dementia, and the number is expected to triple to 152 million by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The mean total score of dementia knowledge among students on all campuses was 15.09 out of 25. The findings indicated that improved knowledge of dementia is required among students [15]. To the best of our knowledge, there is a gap of knowledge considering our topic in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 88%
“…The mean total score of dementia knowledge among students on all campuses was 15.09 out of 25. The findings indicated that improved knowledge of dementia is required among students [15]. To the best of our knowledge, there is a gap of knowledge considering our topic in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 88%